2010
DOI: 10.1007/s00270-010-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Transjugular Intrahepatic Portosystemic Shunt (TIPS)-associated Refractory Hepatic Encephalopathy by Shunt Reduction Using the Parallel Technique: Outcomes of a Retrospective Case Series

Abstract: The parallel technique of TIPS reduction is reproducible and has a high technical success rate. A dual unilateral transjugular approach is advantageous when performing this procedure. The parallel technique allows repeat bidirectional TIPS adjustment and may be of significant clinical benefit in the management of refractory HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
(55 reference statements)
0
10
0
4
Order By: Relevance
“…68 Treatment options for these patients include liver transplantation, reduction/occlusion of the TIPS, and embolisation of portosystemic collaterals. Different techniques have been described to reduce the TIPS, including placement of a suture constrained stent graft within the TIPS, placement of a balloon expandable short stent outside a self-expanding stent graft, 69 adjustable balloon expandable stent graft 70 within the TIPS (Fig 10c,d), and placement of two small parallel stents within the existing TIPS. Shunt occlusion with coils or vascular plugs may be considered as a last resort.…”
Section: Management Of Encephalopathymentioning
confidence: 98%
“…68 Treatment options for these patients include liver transplantation, reduction/occlusion of the TIPS, and embolisation of portosystemic collaterals. Different techniques have been described to reduce the TIPS, including placement of a suture constrained stent graft within the TIPS, placement of a balloon expandable short stent outside a self-expanding stent graft, 69 adjustable balloon expandable stent graft 70 within the TIPS (Fig 10c,d), and placement of two small parallel stents within the existing TIPS. Shunt occlusion with coils or vascular plugs may be considered as a last resort.…”
Section: Management Of Encephalopathymentioning
confidence: 98%
“…19 Since the introduction of covered stents, TIPS reduction has been increasingly performed with better technical and clinical outcome results. One of the most frequently used techniques is the 'parallel technique' [20][21][22] ; this technique includes insertion of a balloon-mounted bare metal stent with a diameter of 6 mm and a length of 2-3 cm in the initial TIPS track and in parallel to this stent, a covered, self-expanding stent with a nominal diameter equal to the initial TIPS-stent graft, is placed. The rigid, balloon-mounted stent will induce a waist to the middle portion of the self-expanding covered stent, resulting in a reduced diameter of the parallel self-expanding stentgraft (►Fig.…”
Section: Interventional Tools To Manage Tips-induced Hepatic Encephal...mentioning
confidence: 99%
“…TIPS reduction preserves TIPS function, reducing exacerbation of portal hypertension while maintaining portal perfusion and hepatic detoxification from gut-derived nitrogenous compounds. 33 For these reasons, endovascular techniques have refined toward stent utilization for graded shunt reduction. 22 There is sparse data on the target PSG post-TIPS reduction.…”
Section: Tips Reduction/occlusionmentioning
confidence: 99%
“…5). 33 Parallel stent grafts allow for biluminal adjustment of shunt diameter to manage the portosystemic pressure gradient to optimize TIPS configuration and flow. 33 Previous trials 33 have demonstrated clinical improvement in 62.5% of their patients and complete resolution of HE in 50% of their patients with the parallel stent graft technique.…”
Section: Parallel Stent Graft Techniquementioning
confidence: 99%